Business Competitiveness Strategies of Tax Consulting Firm amidst Covid-19 Pandemic (Case Study at PT XYZ) - Prianto Budi Saptono; Ismail Khozen (Faculty of Economics, Universitas Sriwijaya, 2021)
This study aims to examine the competitive strategies of companies in facing thechallenges of the Covid-19 pandemic with a case study on a tax consulting firm in Jakarta(